METABOLIC ADAPTATION TO INACTIVE LIFESTYLE: FROM MUSCLE ATROPHY TO CARDIOVASCULAR RISK - Francesco Agostini; Sara Mazzucco; Gianni Biolo (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2010)
Inactivity is known to principally induce muscle atrophy, determined by unbalanced protein synthesis and degradation and to enhance general cardiovascular risk. In parallel, unloading can upregulate whole body oxidative stress and the action of antioxidant factors, as physiological response. This alteration is accompanied by enhanced systemic inflammation. Growing evidence in animal models suggest that inflammation and oxidative stress can play a causative role in inactivity mediated muscle atrophy. The present review is focused on human studies linking inactivity mediated oxidative stress and inflammation to unloading related atrophy. Recent works evidencing enhanced cardiovascular risk after unloading are reported. In addition, evidence regarding the role of inflammation in cardiovascular drawbacks linked to inactivity are discussed.